DEVELOPMENT OF EDUCATIONAL GAME BASED LEARNING ASSESSMENT: PENGEMBANGAN ASESMEN PEMBELAJARAN BERBASIS GAME EDUKASI - Annisa Tiara; Friyatmi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aim to develop an educational game-based learning assessment assisted by Quizwhizzer that is valid and practical for learning assessment activities. It is a research and development with the ADDIE model. The sample of this research were economics teacher and students in senior high schools in Padang. The data were collected using validation sheets and questionnaires. It were analyzed using statistic descriptive. The results show that the product is valid and practical for economics learning.